Integrating Islamic Values into The Development of Announcement and Notice Unit for The Eight Grade in MTs Madani Pao-Pao: Integrating Islamic Values - Zahra, Andi (Journal of Islamic Culture and Literature (JICeL), 2023)
English material that is used in the school is too general. It is also already not reflecting Islam itself. To maintain students identity as Muslim, this  paper is aimed to integrate Islamic Values into English material especially  in  basic  competences  3.12 and 4.12 about Announcement and Notice for the eighth grade students at MTs  Madani  Pao-Pao based  on  2013  curriculum. The research design used in this study was Research and Development (R&D).  The   development   model   used   was   ADDIE   model. It consists of need analysis, design, development, implementation, and evaluation.  The  procedures  included  analyzing  materials   needed   by spreading  questionnaire  to  the  students  and  analyzing  the  basic   competences used, designing a  blueprint  of  materials,   and developing the English materials through ADDIE model. In this research, the expert was involved in order to validate the product. There were two systematic aspects that they validated of the product:  the aspect of the content/material and aspect of learning.  Therefore,  the  result  indicated  that  based on experts judgment as well as  product  development  result,  the  developed basic competences 3.12 and 4.12 was applicable to be taught at the eighth grade students  of  Junior  High  School as topics in English.Keywords: Development, Islamic Values, English Material